2023
DOI: 10.21203/rs.3.rs-2503315/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation and Review of the Care Ecosystem in an Integrated Healthcare System

Abstract: Background and Objectives The University of California, San Francisco Memory and Aging Center (UCSF-MAC) led the development and tested a collaborative care model delivered by lay care team navigators (CTNs) with support from a multidisciplinary team known as the Care Ecosystem (CE). We report the results from the application of the CE within a non-academic healthcare system. Research Design and Methods The CE team at HealthPartners consisted of two CTNs, a social worker, an RN, a program coordinator, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…756,757 A non-academic health care delivery organization which adopted the Care Ecosystem found that the model can be successfully implemented and integrated into purely clinical settings. 758 With regard to cost savings, participation in the Care Ecosystem reduced the total cost of care by $3,290 from 1 to 6 months postenrollment and by $3,027 from 7 to 12 months post-enrollment, corresponding to a mean monthly cost reduction of $526 across 12 months. 757 An implementation toolkit for the Care Ecosystem is publicly available at: https://memory.ucsf.edu/sites/memory.ucsf.edu/files/ wysiwyg/CareEcosystemToolkit.pdf.…”
Section: Collaborative Workforce Models For Dementia Care Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…756,757 A non-academic health care delivery organization which adopted the Care Ecosystem found that the model can be successfully implemented and integrated into purely clinical settings. 758 With regard to cost savings, participation in the Care Ecosystem reduced the total cost of care by $3,290 from 1 to 6 months postenrollment and by $3,027 from 7 to 12 months post-enrollment, corresponding to a mean monthly cost reduction of $526 across 12 months. 757 An implementation toolkit for the Care Ecosystem is publicly available at: https://memory.ucsf.edu/sites/memory.ucsf.edu/files/ wysiwyg/CareEcosystemToolkit.pdf.…”
Section: Collaborative Workforce Models For Dementia Care Managementmentioning
confidence: 99%
“…As a second example, the Care Ecosystem — a collaborative, team‐based dementia care program utilizing telehealth that involved care navigators, advanced practice nurses, social workers and pharmacists — resulted in fewer ambulance rides, emergency department visits and hospitalizations and lower total cost of care compared with usual care 756,757 . A non‐academic health care delivery organization which adopted the Care Ecosystem found that the model can be successfully implemented and integrated into purely clinical settings 758 . With regard to cost savings, participation in the Care Ecosystem reduced the total cost of care by $3,290 from 1 to 6 months post‐enrollment and by $3,027 from 7 to 12 months post‐enrollment, corresponding to a mean monthly cost reduction of $526 across 12 months 757 .…”
Section: Workforcementioning
confidence: 99%